PERAN KELUARGA PADA LANSIA YANG MEMILIKI RESIKO JATUH DI DUSUN SELUR DESA TANGKIL KECAMATAN PANGGUL KABUPATEN TRENGGALEK - Vela Purnamasari; Dwi Murti (STIKES dan AKZI Karya Husada Kediri, 2022)
The role of the family in the elderly who are at risk of falling consists of educators, motivators, and facilitators. Falls in the elderly will cause disability, experience limitations in carrying out daily activities, and decrease quality of life and death. The family has a role as a caregiver in providing actions to prevent the risk of falling in the elderly and improve their quality of life for the elderly to be better. The purpose of the study was to determine the role of the family in the elderly who are at risk of falling in Selur Hamlet, Tangkil Village, Panggul District, Trenggalek Regency. Descriptive design, a population of 227 respondents and a sample of 23 respondents, using purposive sampling technique, the instrument using a questionnaire sheet, the research was carried out on August 26 – September 10, 2022. Variable role of the family in the elderly who have a risk of falling in Dusun Selur, Tangkil Village, Panggul District, Trenggalek Regency. From the results of the study, it was found that almost half of the respondents with good family roles were 39% and most of the respondents with sufficient family roles were 61%. The role of the family is influenced by age, gender, education, living with, the closest family member to the elderly, active participation in the posyandu for the elderly, history of previous falls, history of comorbidities, and use of hearing/vision aids. It is expected that respondents have a good family role and can increase knowledge, and awareness, provide education, motivation, and facilities to prevent the risk of falling in the elderly, and create a situation with minimal risk factors so that the quality of life of the elderly can improve.